(3Qgf GdOjf hJfXje CMcGeg Hjf Gdabg GdESdGej hGdbGfhf GdhVYj (B: s (3HMK ebGQf (B/ s - (3eUWai YHO GdMejO eMehO YjGOs; (3fRjg eMeO GdUGOb GdegOj (B: s; (3jhSa bGSe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1983)
(3jJYQV GdHGH GdJegjOj dgPg GdOQGSg dTQYjg GdQgf HUag YGeg ai Gdabg GdGSdGei hGdbGfhf GdhVYi hJYQja GdQgf hHjGf WHjYg Mb GdOGFf GdeQJgf Ydi GdOjf GdeQghf ceG jJYQV gPG GdHGH dJYQja GdOjf hJMOjO eOdhdg Hjf GdGdJRGe hGdMb GdTNUi CeG GdbSe GdGhd ef GdOQGSI ajHMK ai GfYbGO GdQgf ef MjK GQcGfg hTQhWg hjJYQV dQVGFjg YbO GdQgf hgh ai Pdc jNVY dMce GdbhGYO GdYGeg aj GdYbhO ceG jJYQV ddOjf GdeVehf HGYJHGQI GdGUd ai hLhO GdQgf ceG jHMK ai GdOjf GdeQghf HGYJHGQg eMdG dYbO GdQgf heG jTJQW ajg dci jUHM bGHdG dMce GdQgf ceG jHMK gPG GdbSe ai TQhW faGP Qgf GdOjf ai ehGLgg GdZjQ hgd jNJda GdOjf Yf HbjI GdGehGd GdGNQi ai Pdc Ge dG fXQG dWHjYI GdOjf GdeYfhjg gPG hjJfGhd GdbSe GdKGfi ef GdHMK BKGQ GdQgf hGfbVGAg hGdJRGeGJ GdQGgf hefgG GdJRGeg HJSdje SfO GdOjf GdeQghf eSJhajG cGajI TQhW faGPg ai ehGLgg GdZjQ hGdJRGeg HVeGf SdGeg GdQgf hfaGPg NdGd aJQI bjGe GdQgf hGNjQG GdJRGeg HGdGfaGb Ydi GdeQghf dMaXg hUjGfJg ceG jJYQV gPG GdbSe dHYV Mbhb GdQGgf Ydj eGdg GdeQghf hMbhb GdOGFf GdeQJgf hefgG Mbg ai GdMHS dSfO GdOjf GdeQghf hTQhWg hfWGbg hGgejI gPG GdMb ai MeGjg Mb GdQgf dUGdM GdeQJgf hMb GdJJHY hMb GdJbOe ceG jJYQV gPG GdbSe dGdJRGeGJ GdeQJgf hCgegG GdJRGeg HMaX GdeQghf HMce MjGRJg dg hGdJRGeg HQOg HYO GSJjaGO Mbg cGedG hCNjQG jfGbT gPG GdbSe GfbVGA GdQgf dGf GdQgf ceG jHOC HGdYbO dGHO hGf jfJgj HGMO CSHGH GfbVGFg ShGA HJMbjb GdZGjg efg Ge dG(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2021.s
Keywords: (3GdTQjYI GdESdGejIs; (3TQYjI GdQgfs; (3Mce Qgf GdOjf hfaGPgs; (3UhQ Qgf GdOjfs; (3GfYbGO Qgf GdOjfs; (3BKGQ Qgf GdOjfs; (3GdJRGe GdQGgf HGdGJaGbs; (3VeGf GdSdGeIs; (3Mbhb GdOGFf GdeQJgfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1983